(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Iron deficiency anemia (IDA) is an important global public health issue and a significant problem for children in many lower- and middle-income countries. After years of conflict and economic instability, little information exists to show the prevalence of IDA among children living in urban Baghdad. Objectives: To determine the prevalence of iron deficiency anemia and assess the associated risk indicators. Methods: A cross-sectional study was conducted during the study period (March to August 2024) among 1,247 children aged 6–12 months, selected randomly from households in five different districts of Baghdad. Findings included: demographic information identifying socioeconomic status, dietary intake, and laboratory testing (CBC, ferritin, transferrin saturation, total iron binding capacity). Results: The overall prevalence of iron deficiency anemia was found to be 34.7% (95% CI: 32.1–37.4%). The highest prevalence was found in infants aged 6–24 months (47.8%). The percentage of IDA decreased as age increased. Significant risk factors for IDA included: pocketbook costs of dietary intake (OR=2.34, 95% CI: 1.78–3.08) <1.9% a day (040), maternal anemia (OR=2.67, 95% CI: 2.05–3.48), and low pocketbook cost of dietary intake (1.89 <1.41 <2.47). Conclusion: Iron deficiency anemia is a major problem affecting more than one-third of children in urban Baghdad, with the highest burden in infants and toddlers. There is a great need for interventions both directly regarding the issue of clan and economic support.